IDIOPATHIC LEFT VENTRICULAR TACHYCARDIA: A CASE REPORT - Dyah Ayu Shinta Ratnasari; Ima Ansari Kusuma (Universitas Muhammadiyah Purwokerto, 2018)
ABSTRACTAccurate diagnosis of wide QRS complex tachycardia is difficult in emergent situations. Idiopathic Left Ventricular Tachycardia (ILVT) is a ventricular tachycardia characterized by right bundle branch block (RBBB) and left axis deviation (LAD) on electrocardiogram, its accounts for 10-15% of all left ventricular tachycardias. We present case of ILVT in a young 32-year-old gentleman presenting with unstable hemodynamic and a wide-complex right bundle, left axis deviation on electrocardiogram. Electrical cardioversion was given and the ILVT was terminated. Verapamil 80 mg twice daily was given, and he planned to radiofrequency ablation. It is important for emergency physicians to recognize the electrocardiographic features of ILVT and to manage these patients appropriately.